KAJIAN KINERJA PERUSAHAAN DAERAH AIR MINUM BANDARMASIH KOTA BANJARMASIN DAN KEPUASAN PELANGGAN DALAM UPAYA PENINGKATAN KUALITAS PELAYANAN TESIS - , MUHAMMAD SYARMANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PDAM Bandarmasih as drinking water management company in Banjarmasin required to meet the needs of clean water with quality, quantity and continuity of qualified and reliable. Along with the increasing economic movement, accompanied by relatively high population growth, the development of residential and industrial development that continues to rise to the challenge for PDAM to improve its service. On the other hand, most customers are still complaining about the service of PDAM both in terms of quality, quantity and continuity of water. There are also complaints about water metering, water bill payment system, which is considered most customer rates are still high and also on the handling of complaints that are considered less of responsive. The method used in this research is to process the primary data in the form of customer satisfaction questionnaire first tested for validity and reliability with SPSS software and secondary data in the form of an interview with the Director of PDAM, finance, administration, and technical staff. Measuring performance of PDAM using Kepmendagri No. 74 of 1999 as well as qualitative and quantitative analysis of the value of customer satisfaction, and decision-making method using the Analytic Hierarchy Process (AHP). Results of customer satisfaction analysis shows that the current state of the most satisfying water quantity value is 3.79 and that is considered the least satisfactory is the billing system and payment procedures with a value of 3.65. PDAM Bandarmasih performance for the financial, operational and administration are included in good category with score 73. The results of the decision-making analysis with the AHP of the three alternatives available, Alternative âAâ received the highest score with value 0.4405, by way of a third party involvement for the new investment and management a comprehensive priority vector.